Adherence to walking exercise prescription during pulmonary rehabilitation in COPD with a commercial activity monitor: a feasibility trial - Sarah Ward; Mark Orme; Jakub Zatloukal; Sally Singh (BMC Pulmonary Medicine, 2021)
Abstract Background Regular exercise is important in the management of COPD. Pulmonary rehabilitation (PR) facilitates a more physically active lifestyle through exercise participation, ideally without compromising non-exercise physical activity (PA). During PR patients are advised to perform exercise defined by duration and intensity. The extent to which PR attendees participate in unsupervised exercise bouts and their adherence to the exercise prescription provided during PR is unclear. Commercially available devices have the potential to support patients to exercise at their individually prescribed intensity. Study aims were to (1) assess how adherent patients are to their prescribed walking intensity; (2) examine the pattern of overall PA and walking exercise during the course of PR; (3) determine the feasibility of prescribing exercise to PR attendees using an activity monitor; and (4) explore the relationship between exercise and non-exercise PA with routine PR outcome measures. Methods 19 patients wore an activity monitor during routine walking tests and 6 weeks of PR, recording in a diary when they exercised. Exercise intensity (cadence) was prescribed from the Endurance Shuttle Walk Test. Patients completed questionnaires, walking tests and a lower limb strength test before and after PR. Repeated ANOVA compared changes in outcomes between weeks 1–6. Results Patients wore the monitor every day during PR (median 42 days). Exercise steps increased by 56% (Δ332 [95% CI 54–611] steps/day, p = 0.009) between weeks 1 and 6, with no significant change in non-exercise steps (Δ79 [95% CI − 22 to − 179] steps/day, p = 0.13). Patients reported exercising on 70% of days. Adherence to prescribed cadence was achieved 55% of time spent exercising, and did not change across the 6 weeks (p = 0.907). Change in total daily steps was associated with improved dyspnea (p = 0.027), Chronic Respiratory Questionnaire (CRQ) Dyspnea domain (p = 0.019), CRQ Emotional Functioning domain (p = 0.001) and CRQ Mastery domain scores (p = 0.001) but not with exercise capacity or lower limb muscle strength. Conclusions Improvements in exercise participation, not at the expense of non-exercise PA, throughout a PR course was observed in attendees provided with a commercially available activity monitor. Wearable technology may be able to support effective remote walking exercise prescription and participation during PR. Trial registration (retrospectively registered): http://www.isrctn.com/ISRCTN15892972 .